1991
DOI: 10.1007/bf00040632
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cDNA clones for NADP-malic enzyme from leaves ofFlaveria: transcript abundance distinguishes C3, C3?C4 and C4 photosynthetic types

Abstract: To study the control of enhanced synthesis of enzymes associated with C4 photosynthesis relative to non-C4 plants, we investigated the expression of NADP-malic enzyme (NADP-ME) in different photosynthetic types of Flaveria. Complementary DNA clones encoding NADP-ME were constructed using poly(A)+ RNA from leaves of Flaveria trinervia (C4) and F. linearis (C3-C4) and identified by homology to a cDNA clone (500 bp) encoding NADP-ME from maize (Zea mays L. [39]). The sequence of one clone from each species was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…This cDNA, termed hmell, was identified using a maize NADP-ME cDNA (Rothermel and Nelson, 1989) as probe. The nucleotide sequence of Ame11 was >99% identical with that of the middle region of two NADP-ME cDNAs previously reported to encode the C, form of the enzyme in the closely related species F. trinervia (data not shown; Borsch and Westhoff, 1990;Rajeevan et al, 1991).…”
Section: Cenomic Clonesmentioning
confidence: 52%
See 4 more Smart Citations
“…This cDNA, termed hmell, was identified using a maize NADP-ME cDNA (Rothermel and Nelson, 1989) as probe. The nucleotide sequence of Ame11 was >99% identical with that of the middle region of two NADP-ME cDNAs previously reported to encode the C, form of the enzyme in the closely related species F. trinervia (data not shown; Borsch and Westhoff, 1990;Rajeevan et al, 1991).…”
Section: Cenomic Clonesmentioning
confidence: 52%
“…3C). Furthermore, comparison of the 3' UTR of the reported partia1 NADP-ME cDNA from the C,-C, intermediate species F. linearis (Rajeevan et al, 1991) with those of Mel and Me2 indicated that the F. linearis cDNA, like the F. pringlei cDNA, was much more similar to Me2 than to Mel (data not shown).…”
Section: Sequence Analysis Of Mel and Me2mentioning
confidence: 97%
See 3 more Smart Citations